Interpretation of Tracer Experiments on Inverted Five-spot Well-patterns within the Western Half of the Farnsworth Unit Oil Field. (July 2017) - White, M.D.; Esser, R.P.; McPherson, B.P.; Balch, R.S.; Liu, N.; Rose, P.E.; Garcia, L.; Ampomah, W.
Abstract: The Southwest Regional Partnership on Carbon Sequestration (SWP), one of the U.S. Department of Energy (U.S. DOE) seven Regional Carbon Sequestration Partnerships, is currently working to demonstrate the utilization and storage of CO2 in the Farnsworth Unit (FWU) Enhanced Oil Recovery (EOR) site under the final development phase of this U.S. DOE initiative. A component of the research is to use fluid tracers to understand the multifluid flow patterns that develop between injection and production wells via collected field data and supporting numerical reservoir models. The FWU, located in the Anadarko Basin, Ochiltree County, Texas, and being operated by Chaparral Energy, is a mature EOR water-flood field, which is currently being converted to a CO2 flow, with inverted 5-spot patterns transitioning from pure water to alternating CO2 and water floods (i.e., water alternating gas (WAG)) at an approximate rate of one every 6 to 10 months. The SWP tracer program is conducting a suite of tracer injections into the active 5-spot patterns at the FWU. Tracers have been selected to be nonreactive and either principally soluble in CO2 (gas soluble) or water (aqueous soluble). In addition to characterizing the multifluid flow behaviour within reservoir, the gas and aqueous tracers have roles in detecting any leakage from the reservoir. A total of seven unique perfluorocarbon tracer (PFT) compounds make up the suite of gas soluble tracers and eight unique naphthalene sulfonate tracer (NPT) compounds comprise the aqueous soluble tracers. All selected tracers are significantly detectable below the parts per billion concentrations, allowing for high resolution for the inter-well tests at relatively low injection volumes.